Pengaruh Variasi Produk, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Barang Preloved Di Pasar Thrift, Stadion Diponegoro, Kota Semarang - Zamani, Daffa Ulya; Amron, Amron; Waluyo, Dwi Eko; Puspitasari, Diana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The purpose of this study is to examine how product quality, price, and variety affect consumers' decisions to buy used items in Pasar Murah, Diponegoro Stadium, Semarang City. One hundred customers at Pasar Murah, Diponegoro Stadium, Semarang City, participated in a quantitative study. Questionnaires were used to gather data, and multiple linear regression analysis and traditional assumption tests were used for analysis. The findings demonstrated that when it came to purchasing used products at Pasar Murah, product variety, price, and quality all had a favorable and substantial impact. This implies that customers are more likely to buy used items when the product variety is more diverse, the pricing is more competitive, and the product quality is higher. In order to enhance client purchase decisions, this study offers sellers of pre-owned items practical recommendations for how to keep developing more diverse product variants, more competitive pricing, and higher product quality.